“Is Inclusive Education Inclusive Enough?”: Portraying Student with Disabilities’ Experiences on Immersive Learning - Ashar, Muhammad Nurul; Evans, David; Murtadlo, Murtadlo; Pamuji, Pamuji; Beny, Acep Ovel Novari (Angstrom Centre of Education, 2024)
Inclusive education holds the important role on developing students’ understanding and character on inclusivity during teaching students with disabilities. Thus, an appropriate teaching method should be assigned on this course. Immersive learning has previously been studied in improving the learning gain for many students, however its application in inclusive education course has rarely been done. This study portrayed the students with disabilities experience on studying inclusive education course with immersive learning. Their experiences were explored on two main aspects including the reception towards immersive learning, and the inclusivity of the immersive learning. Data were collected through test and close-ended questionnaire from nearly thirty students after the intervention. Responses from test were analyzed statistically with Wilcoxon test, while data from questionnaire were analyzed using the statistic descriptive. Results report that students perform a positive outcome after the intervention session with many feel that the lesson is more inclusive. Statistic also shows the difference on students score before and after the lesion. This happened either for students with disability or students without disability. This study may provide a new way of teaching for students with disability, yet further studies are still needed.